Hilary Putnam: La transformación de la filosofía - Di Santo, Laura Balvanera (2016)
Hilary Putnam makes a diagnosis on the current situation of philosophy and resolve that it is necessary to undertake its renovation. He notes that the contemporary reflection is trapped in the middle of two extreme positions: relativism and scientism. We analyze in this work how both tendencies provide, to the debate on realism, two extreme conceptions of rationality with strong impact for the practice of our discipline and for men’s life. This situation takes our author to offer “a proposal to renew philosophy” which, as we intend to show, involves a change in attitude, a new way of approaching the nature of philosophical questions and of outlining their answers. The development of his own thought represents a sample of this revitalization project, which involves the emergence of new interests and a vital transformation on philosophy’s function.